Are Group Interventions Effective at Improving Health Outcomes in Culturally And Linguistically Diverse (CALD) Populations With Chronic Conditions? An Umbrella Review - Karma Phuentsho; Emma L. Karran; Ruth P. Appiah; Marinelle Fernandez; Kristin Graham; Saravana Kumar; Saurab Sharma; Amanda C de C Williams; Aparnadas Amritha; G. Lorimer Moseley (Journal of Immigrant and Minority Health, 2026)
Abstract Culturally and linguistically diverse (CALD) populations experience disproportionate burdens of chronic disease compared to the general population; previous research demonstrated group-based interventions improve health outcomes across various chronic conditions. This umbrella review aims to summarise the available evidence concerning group-based interventions for CALD populations with chronic conditions. We conducted this umbrella review in accordance with the Cochrane Handbook for Systematic Reviews of Interventions , reported per PRISMA, and quality-assessed using AMSTAR-2 (A MeaSurement Tool to Assess systematic Reviews, version 2). We searched 11 databases (MEDLINE, Embase, Emcare, CINAHL, PsycINFO, SCOPUS, Web of Science, Cochrane, Epistemonikos, LILACS, and SciELO citation index of Web of Science) from inception to June 3, 2025, without language restrictions. All screening, data extraction, and quality assessment were carried out in duplicate. We descriptively synthesised the findings and determined the effectiveness and effect sizes of interventions as concluded by the review authors. We identified 22 systematic reviews, 271 primary studies, and over 32,320 people. Reviews originated from high-income countries; published in the last 10 years (82%); most (13) scored low on AMSTAR-2 quality rating. Reviews were related to mental health conditions (15), diabetes (4), chronic pain (1), cancer (1), and mixed chronic health conditions (1). Group-based Psychological Interventions reported positive effects on depression, anxiety, and PTSD symptoms, well-being, and quality of life. Educational Interventions improved diabetes outcomes (notably glycated haemoglobin), psychosocial outcomes in mental health, and pain, fatigue, physical activity, and self-efficacy in other chronic conditions. Multimodal Interventions improved psychosocial outcomes for mental health, pain, and disability outcomes for chronic pain. Some reviews reported mixed findings or insignificant effects. Overall, group-based interventions improved health, mental well-being, and biopsychosocial outcomes in CALD populations with chronic conditions. However, evidence remains limited; study heterogeneity (interventions, populations, outcomes) was marked. Future research should prioritise clearly describing the development, design, and implementation of interventions to meet the complex and diverse needs of CALD populations.